Driven into paradise : the musical migration from Nazi Germany to the United States - Brinkmann, Reinhold, 1934-2010; Wolff, Christoph (University of California Press, 1999)
"The Forced Migration of artists and scholars from Nazi German is a compelling and often wrenching story. The story is twofold - of impoverishment for the countries the musicians left behind and enrichment for the United States. The latter is the focus of this collection, which approaches the subject from diverse perspectives, including documentary-style newspaper accounts and an exploration of Walt Whitman's poetry in the work of Paul Hindemith and Kurt Weill."--Jacket.